Always and forever Lara Jean - Han, Jenny (New York: Simon & Schuster BFYR, 2017)
As high school ends, Lara Jean looks forward to her father's remarriage and seeing her sister, but she must choose a college, prepare to leave home, and possibly leave her beloved Peter behind.
New York Times Bestselling author, Jenny Han
Keywords: Love -- Fiction; College choice -- Fiction; Lara Jean (Fictitious character); Young adult fiction